PENGARUH AMELIORAN DALAM MENGEFISIENKAN PENGGUNAAN PUPUK P PADA TANAMAN PADI GOGO (Oryza sativa L.) VARIETAS SITU BAGENDIT DI TANAH ULTISOL - Nadiya Pirhat; Idwar '; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research intent to know ameliorant influence to efficient using of P fertilizers and the best recommanded for growth and production of upland rice (Oryza sativa L.) Situ Bagendit variety on ultisol. Research conducted in UPT area of research farm in faculty of agriculture, Riau University on Bina Widya Campus Km 12,5 sub-district of Simpang Baru, district of Tampan, Pekanbaru from December 2014 until Mei 2015. This research arranged experimentally by using Completely Randomized Design which consist of 9 treatments and then obtained 27 experimental units with 3 sample each unit. Parameter observed rate of P, efficient of P absorption, efficient of production gram of grain rice, ameliorant influence in the efficient to absorp P fertilizer, ameliorant influence in the efficient to product of grain rice, plant height, productive tiller number, panicle length, the percentage of pithy grain, 1000 seed weight, dry of grain weight/family and dry plant of weight. Data were analyzed statistically using ANOVA and followed by HSD at level of 5%. The result showed that giving ameliorant be BFA 12,5 g, green manure of krinyuh 12,5 g and green manure of krinyuh 12,5 g + BFA 12,5 g can give the best result in rate of P, efficient of P absorption, efficient of production gram of grain rice, ameliorant influence in the efficient to absorp P fertilizer, productive tiller number, plant height, dry of grain weight/family and dry plant of weight. Keywords : ameliorant, P fertilizer, upland rice, ultisol.